The TRIPS Agreement in Combatting Covid-19 : Compulsory Licencing and Timely Access to Vaccines - Dunder, Tuuli (My University, 2021)
This thesis examines the role of the WTO TRIPS Agreement in combatting delays in pandemic-related vaccine distribution. The patent regulation of the TRIPS Agreement provides a limited number of exceptions to the patent holder's exclusive rights, the most relevant during pandemics being the combination of Art. 31 and 31 bis: compulsory licencing. This thesis focuses on investigating whether the compulsory licencing system manages to adequately respond to issues related to global timely access to vaccines. The topic of the thesis was selected as after the outbreak of the Covid-19 pandemic, broad discussion on the role of the TRIPS regulation began. This thesis investigates the most relevant factors behind the unequal global distribution of vaccines during pandemics and provides an analysis on whether the TRIPS regulation may serve as a solution for these issues. The study is conducted by a legal dogmatic method, relying on economic argumentation from relevant parts. Primary sources are the Resource Book on TRIPS and Development by the WTO and WTO official documents regarding the compulsory licencing system and Covid-19 pandemic. The key research findings are that although the compulsory licencing system is a flexible tool and may serve as an effective post-pandemic tool in keeping the prices of voluntary licences competitive, it does not offer a comprehensive solution to pandemic-related delays in vaccine distribution. The weakness of the system derives from the fact that one of the most significant factors behind the timely distribution of vaccines is the inadequate global manufacturing capacity, which is further aggravated by granting exclusive patent rights to vaccine developers. Furthermore, Art. 39 TRIPS prevents the efficient use of the compulsory licencing system by blocking the dissemination of know-how and technology. The TRIPS Agreement has been drafted to protect private property rights and to support the dissemination of technology in the long term, whereas during pandemics, the balance should be more on global health considerations and on the dissemination of technology and know-how in a rapid timeframe. Thus, it is suggested that a new regulative framework should be mutually negotiated for future pandemics. This framework should be construed by taking into account the difficulties in global manufacturing capacity and the role of exclusive patent protection to these issues thereof. However, also the financial interests of pharmaceutical actors shall be considered to preserve the incentives for research and development.

Tämä tutkielma käsittelee Maailmankauppajärjestön TRIPS sopimuksen roolia rokotteiden tasapuoliseen ja nopeaan saatavuuteen liittyvissä ongelmissa. TRIPS sopimuksen patenttisääntely tarjoaa rajallisesti poikkeuksia patentinhaltijoiden muuten eksklusiivisiin oikeuksiin. Pandemioiden kannalta poikkeuksista relevantein on sopimuksen artiklat 31 ja 31bis, jotka muodostavat yhdessä pohjan pakkolisensoinnille. Tässä tutkielmassa on keskitytty tutkimaan sitä, onko pakkolisensoinnilla mahdollista vastata pandemian aiheuttamiin rokotesaatavuuden haasteisiin, ja millä mittapuulla. Tutkielman aihe valikoitui Covid-19 pandemian herättämän TRIPS sopimukseen liittyvän laajan keskustelun myötä. Keskustelun innoittamana tutkielmassa on paneuduttu niihin tekijöihin, jotka ovat keskeisessä roolissa rokotteiden tasapuolisen ja nopean saatavuuden kannalta, sekä otettu kantaa siihen, pystyykö TRIPS sopimus vastaamaan näiden tekijöiden asettamiin haasteisiin. Tutkimus on oikeusdogmaattinen, ja siinä hyödynnetään soveltuvin osin taloudellisia argumentteja sekä tukeudutaan yhteiskunnalliseen keskusteluun. Päälähteinä on käytetty Maailmankauppajärjestön tuottamaa kirjallisuutta TRIPS sopimuksen tulkintaan liittyen (Resource Book on TRIPS and Development) sekä Maailmankauppajärjestön virallislähteitä pakkolisensointiin sekä Covid-19 pandemiaan liittyen. Tutkielman johtopäätös on, että artiklat on suunniteltu joustaviksi, ja pakkolisensoinnilla pystytään mahdollisesti pitämään pandemian jälkeiset lisenssihinnat matalina. Huolimatta näistä hyvistä puolista. pakkolisensoinnilla ei kuitenkaan pystytä kokonaisvaltaisesti vastaamaan pandemian asettamiin haasteisiin. Oikeudellisen kehikon heikkoudet ovat tulosta puutteellisesta globaalista rokotteiden valmistuskapasiteetista, jota TRIPS sopimuksen mukainen eksklusiivinen patenttien suoja vakavoittaa entisestään. Näitä ongelmia korostaa myös TRIPS sopimuksen 39 artikla, jonka vuoksi rokotteisiin liittyvän teknologian ja asiantuntijuuden levittäminen globaalisti on erittäin vaikeaa. TRIPS sopimus on laadittu yksityisten toimijoiden omaisuudensuojan varmistamiseksi, tähdäten teknologian globaaliin levittämiseen pitkällä aikavälillä. Pandemiatilanteessa insentiivit ovat päinvastaiset: terveyshaittojen ratkaisemisen tulisi olla keskiössä, ja teknologian sekä osaamisen levittämisen tulisi tapahtua mahdollisimman nopealla aikavälillä. Tästä johtuen tutkielmassa ehdotetaan, että tulevia pandemioita varten neuvoteltaisiin täysin uusi lainsäädäntökehikko. Neuvotteluissa tulisi ottaa huomioon globaalissa rokotteiden valmistuskapasiteetissa havaitut ongelmat sekä patenttien suojan rooli kyseisissä ongelmissa. Erittäin tärkeää on myös huomioida yksityisten lääkeyritysten taloudelliset intressit, jotta insentiivit tehokkaaseen rokotteiden tutkimus- ja kehitystyöhön eivät heikkene.
Keywords: TRIPS Agreement, compulsory licencing, pandemics, timely access to vaccines, manufacturing capacity, transfer of technology, dissemination of know-how